PEREMPUAN DAN PERSPEKTIF GENDER DALAM PENULISAN SEJARAH INDONESIA - Dias Pradadimara (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
This paper tries to see the development of historical writings in general and particularly in Indonesia, especially the ones that focus their attention on women. It discusses the various works by historians in Indonesia and abroad where the emerging gender studies have influenced the ways history is written. From the readings of these works, it can be concluded that there are two main streams of writing the first being more descriptive and the other more causal. The descriptive works tend to look at notable women (beginning with but not limited to Kartini), women-organizations and women’s movements. The causal works tends to be more theoretical and realizing that women and femininity as categories are historical and they look at the ways these categories serve as the bases of the making and maintenance of hirarchies and hegemonic masculinity from colonial eras to the post-colonial world. Keywords: Indonesian histories, historiography, women, gender studies